The Relationship between Body Image and Self-Esteem and the Tendency of Body Dysmorphic Disorder in Class X and XI Adolescents at SMA Muhammadiyah 5 Jakarta - Rachmayadi, Ravena; Askina, Meutia; Safira Sekar Putri, Azzahra (International Journal of Social Science, Education, Communication and Economics, 2024)
The aim of this research is to determine the relationship between body image and self-esteem and the tendency for body dysmorphic disorder in teenagers in grades X and XI at SMA Muhammadiyah 5 Jakarta. The sampling method for this research used a purposive sampling technique and the sample used was 148 teenagers. Based on the results of data analysis using bivariate correlation between body image variables and body dysmorphic disorder tendencies, r = -0.268 with p = 0.001, which means there is a negative relationship between self-esteem variables and body dysmorphic disorder. The results of data analysis between the self-esteem variable and body dysmorphic disorder obtained a correlation coefficient value of r = -0.254 and p = 0.002, which means there is a negative relationship between the self-esteem variable and the tendency for body dysmorphic disorder. Multivariate correlation in the regression test shows that the coefficient of determination R Square is 0.074. Based on the multivariate correlation regression, the correlation coefficient value R = 0.272 and p = 0.004 is obtained, which means there is a relationship between body image and self-esteem and the tendency for body dysmorphic disorder. The effective contribution of body image and price to the tendency for body dysmorphic disorders is 7.4%, while 92.6% is a contribution from other factors not studied.